Association of quality of life with marital satisfaction, stress, and anxiety in middle-aged women - Rakhshani, Tayebeh; Amirsafavi, Masoumeh; Motazedian, Nasrin; Harsini, Pooyan Afzali; Kamyab, Amirhossein; Jeihooni, Ali Khani (Frontiers in Psychology, 2024)
Background: Marital satisfaction is one of the important components of quality of life. Women's marital satisfaction is affected when they enter the middle age period, due to the mental and emotional tensions caused by the physical changes. In this regard, the present study aimed to investigate the association of quality of life with marital satisfaction, stress, and anxiety in middle-aged women referring to health centers of Ahvaz city, Iran.This cross-sectional descriptive-analytical study was conducted on 1000 middleaged married women (30-59 year of age) under the auspices of health centers of Ahvaz city, Iran in 2019. The subjects were selected by simple random sampling method, and were asked to complete demographic characteristics, quality of life questionnaire, Enrich marital satisfaction questionnaire, Holmes-Raheh stress questionnaire, and Spielberger state-trait anxiety inventory. The data were analyzed by using SPSS .22 software through mean, standard deviation, frequency, Pearson correlation and regression (P=0.05).Results: Based on the results, 42.4% of the participants were between 40-50 years of age, 35.6% had a high school diploma, and 50% of them were housewives. Also, the results of Pearson's correlation showed a positive and significant relationship between quality of life and marital satisfaction (r=0.178) (P<0.001). However, quality of life had a negative and significant relationship with anxiety (r=-0.552) (P<0.001) and stress (r=-0.188) (P<0.001).Given the positive and significant relationship between quality of life and marital satisfaction, appropriate trainings are highly recommended for couples to increase the quality of life and marital satisfaction of middle-aged women and thus strengthen the health of family and society.